Cognitive Gain or Handicap: Magical Ideation and Self-Absorption in Clinical and Non-clinical Participants - Kállai, János; Vincze, Gábor; Török, Imre András; Hargitai, Rita; Rózsa, Sándor; Hartung, István; Tamás, István; Láng, András; Herold, Róbert (Frontiers in Psychology, 2021)
Background: This study aimed to examine magical ideation and absorption traits across non-clinical and clinical groups to determine their potential adaptive and maladaptive functions. Method: We enrolled 760 healthy participants from neighboring communities (females = 53.2%). Moreover, we recruited 318 patients (females = 66.5%), which included 25, 183, and 110 patients with schizophrenia spectrum disorders, anxiety disorders, and mood disorders, respectively. Potentially adaptive and maladaptive socio-cognitive functions were measured to determine the role of magical ideation and self-absorption in patients with psychiatric disorders. Results: The degree of magical ideation and absorption gradually increased in the following order: anxiety disorders, mood disorders, and schizophrenia spectrum disorders. Furthermore, enhanced self-absorption-related enhanced consciousness traits were essential indicators of the presence of self-integration weakness in patients with schizophrenia spectrum disorders. Conclusion: Magical ideation and psychological absorption may be considered as mental model construction functions, which result in both gains and handicaps in social adaptation.